SWEET SORGHUM: BROTH CLARIFICATION WITH ENZYMATIC TREATMENT INCREASES THE QUALITY OF THE FERMENTATION WORT FOR ETHANOL PRODUCTION - Ferreira, Osania Emerenciano; Costa, Gustavo Henrique Gravatim; Silva, Aline Ferreira [UNESP]; Montijo, Nayara Abrão [UNESP]; Mutton, Miguel Angelo [UNESP]; Mutton, Márcia Justino Rossini [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2021)
Sweet sorghum is currently being evaluated throughout the world as a raw material for biofuel production because its stem juices are rich in sugars that can be directly fermented to ethanol. In this work, the fermentative efficiency of three sweet sorghum genotypes was evaluated, aiming at ethanol production, harvested in two seasons, clean and whole stems, and the treatment of the juice and broth with amylolytic enzymes in order to use the present starch to increase the production of ethanol. The experiment was carried out in the 2013/2014 harvest, in the municipality of Jaboticabal, São Paulo, Brasil, located at 21°14’05’’S and 48°17’09’’W. The experimental design was completely randomized, with sub-subdivided plots and four replications. The primary treatments were the sweet sorghum genotypes (CV147, CV198, and BRS508), the secondary treatments, the type of harvest (whole stems and clean stems); the tertiary the two sampling times (102 and 116 days after sowing-d.a.s) and the quaternary the application of enzymes. In the fermentation process, the yeast PE-2 was used, at the end, the wine was recovered and characterized. Fermentation efficiency and liters of ethanol per ton of sorghum were calculated. The clarification of the juice with enzymatic treatment increases the quality of the fermentation broth and makes it possible to obtain wines with lower levels of RRTs and Brix. Fermentation efficiency is not affected by the genotype; however, it is influenced by the time of harvest and the technological quality of the juice. The use of amylolytic enzymes makes it possible to obtain wines with lower levels of RRTS and Brix. The best period of industrialization was at 102 d.a.s., and the processing of whole stalks resulted in less ethanol production.
Keywords: Alpha-Amylase; Amyloglucosidase; Bioenergy; Biofuels; Fermentation